STUDY ON THE OPTIMIZATION OF MULBERRY LEAF EXTRACT BY MACERATING ETHANOL AND MICROWAVE ASSISTED EXTRACTION METHOD (MAE) WITH NATURAL DEEP EUTECTIC SOLVENTS (NADES) - Kunaedi, Aan; Indawati, Iin; Karlina, Nina; Fadhillah, Zakie; Cantika, Citra Dhea; Khulfiah, Ade Ayu (Jurnal Farmasi Sains dan Praktis, 2023)
Ethanol extract from the leaves of Morus alba, an herb, has been widely used for medicine, including commercial formulations. This study aims to compare the characteristics of NADES extract using the MAE method and the maceration method. Mulberry leaf simplicia (Morus alba. L) ethanol extract was made with various ethanol concentrations of 50%, 60%, 70%, 80%, and 90%, and NADES (Natural Deep Eutectic Solvents) extract with a solvent ratio of 1:20 and 1: 30 on the MAE (Microwave Assisted Extraction) method with a time of 5 and 10 minutes. Measurement of total flavonoid content and total phenolic content was carried out by UV-vis spectrophotometry with quercetin and gallic acid as reference standards. The results showed that the ethanol extract with ethanol concentrations of 50%, 60%, 70%, 80%, and 90% had an average total flavonoid content; and total phenolic: 0.73%, 0.9%, 1.32%, 1.18%, 0.77%; total phenolic 96.789 mg/g, 71.262 mg/g, 126.465 mg/g, 116.643 mg/g, 93.366 mg/g. NADES extract with a solvent ratio of 1:20 at MAE 5" and 10" minutes obtained flavonoid levels of 0.36%, 0.4%, and total phenolic levels of 36.099 mg/g; 75.621 mg/g. While a ratio of 1:30 with an MAE time of 5" and 10" minutes, the flavonoid content was 0.44%; 0.48%, and the total phenolic content of 61.884 mg/g; 121.237 mg/g. Results of water-soluble essence of ethanol extract; NADES is 26%–31%; 21–24%. Result of ethanol soluble extract content of ethanol extract; NADES is in the range of 36%–42%; 85%–86%. Result of the specific gravity of ethanol extract; NADES is in the range of 0.82 g/mL–0.95 g/mL; 1.08 g/mL–1.18 g/mL. The ethanol extract pH test results were; NADES in the range 6.90–7.01; 7.59–7.89.